1984
DOI: 10.1902/jop.1984.55.3.135
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Reattachment After Gingivectomy in the Rat

Abstract: It is known that an epithelial reattachment occurs a few days after gingivectomy. Depending upon the surgical procedure and the animal species used, different times have been proposed to obtain a complete reattachment. Nevertheless, it is not known whether there is a correlation between the time required and the sequence of morphologic events involved in this process. To investigate this matter, gingivectomies were performed in the maxillary molars of rats. Specimens were taken 1 to 14 days after the operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The primary JE is believed to be formed by the fusion of the reduced enamel epithelium with the oral epithelium and gradually replaced by the oral epithelium6132728. Two proteins, odontogenic ameloblast-associated protein and amelotin, which have the potential to create the enamel, have been identified in the JE and observed during the formation and regeneration of the JE171819.…”
Section: Discussionmentioning
confidence: 99%
“…The primary JE is believed to be formed by the fusion of the reduced enamel epithelium with the oral epithelium and gradually replaced by the oral epithelium6132728. Two proteins, odontogenic ameloblast-associated protein and amelotin, which have the potential to create the enamel, have been identified in the JE and observed during the formation and regeneration of the JE171819.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments using rats have indicated that the oral epithelium proliferates at 2 days post-gingivectomy; the regenerating epithelium then stratifies and keratinizes, with subsequent proliferation of connective tissue. Finally, regeneration of the junctional epithelium leads to completion of gingival regeneration by adhesion to the cemento-enamel junction (CEJ) and enamel surface (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…For tooth movement, an orthodontic elastic module (3M Unitek, St Paul, MN, USA) was placed between the first and the second maxillary molars (18). Removal of the gingiva and the JE along the maxillary molars (gingivectomy) was accomplished by scraping the tooth surface and extending 2 mm along the palate with periodontal curettes (SU 15/33, SL 5/6 and KS 1/2; Hi-Friedy, Chicago, IL, USA) (19).…”
Section: Periodontal Challenge Proceduresmentioning
confidence: 99%